THE ROLE OF THE DIGITAL ECONOMY IN THE DEVELOPMENT OF ACCOUNTING AND AUDIT - Eshmamatova Madina (International Journal of Innovations in Engineering Research and Technology, 2021)
This article discusses modern approaches to the development of auditing in the context of the development of state policy in the field of the digital economy. The foreign experience of recognition of new objects and tools of digital economy is analyzed. The favorable and unfavorable influence of the digital economy on the activity of operating enterprises is revealed. In particular, the technology of the distributed registry (lock-up), crypto-currencies, robotization, the Internet of things, the expansion of business opportunities in the market and the absence of common rules for the use of these tools threaten existing enterprises